BUNG KARNO’S SPEECH AND PANCASILA FOR WORLD PEACE - Djumala, Darmansjah; Djuyandi, Yusa (Universitas Padjadjaran, 2023)
The purpose of this study to analyze the stored ideas so that not simply forgotten and left as archives, so that they benefit the world. This study uses a qualitative method. The analysis was carried out by interpreting the data based on the literature study. Data were collected from primary data and secondary data. Primary data was obtained from interviews, and secondary data from previous reference journals, books, and news from internet sources. This study concludes, Pancasila can become an international reference. With the designation of Bung Karno’s speech entitled “To Build the World Anew” as Memory of the World, it became easier for the international public to access the text archive of the speech as a reference for developing studies. This is because the text of the speech is open for use by researchers, academics and international practitioners in studying Pancasila as a philosophical and political discipline, whose values are very relevant for mediating socio-cultural conflicts.